O serviço de convivência e fortalecimento de vínculos para pessoas idosas na assistência social e o período de isolamento devido a pandemia da covid 19 - Concentino, Luiz Henrique (Universidade Federal de São Carlos, 2023)
The descriptive and exploratory research was carried out in Social Assistance Reference Centers (CRAS) of a city in the interior of the state of São Paulo. The CRAS performs basic social protection services in the territory, offers among the services offered to the population, opportunity of coexistence for people through the Service of Coexistence and Strengthening of Ties. The target audience of the research are elderly people who participated in the Service of Coexistence and Strengthening of Bonds. The objective is to describe the perception of elderly people about participation in the Service of Coexistence and Strengthening of Bonds, at the moment before the Covid-19 pandemic, considering strengths and challenges of face-to-face experiences, as well as verifying the existence of relationships between sociodemographic variables, mood and social support in social isolation in the Covid-19 pandemic. The theoretical framework used is based on historical-dialectical materialism. Data collection was performed with a sample of 30 elderly individuals in person. For the interview, a semi-structured questionnaire was used and two screening instruments were applied: the Minimum Map of Elderly Relationships (MMRI) and the Geriatric Depression Scale (GDS). The results of the GDS showed that 26.7% presented signs of depressive symptoms and 73.3% did not present depressive signs. There was a moderate correlation between those who showed signs of depressive symptoms and younger elderly. It can also be identified that elderly who indicated perception of medium/low social support in the MMRI in emotional function (often), showed signs of mild depressive symptoms in their majority. It can be concluded that public policies offered to the elderly population, such as social groups, are spaces that offer social support, in addition to providing experiences in positive and pleasurable activities and thus end up benefiting mental health.
The service of coexistence and strengthening of bonds for elderly people in social assistance and the period of isolation due to the covid 19 pandemic
Keywords: Idoso; Serviços de Assistência Social; Apoio Social; Sintomas depressivos; Isolamento social; Older adults; Social Welfare Services; Social support; Depressive symptoms; Social isolation; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL